The Role of Interactive Technology in Inclusive Education: A Case Study - Sri Rahayu (International Journal of Educational Research Excellence (IJERE), 2023)
Nowadays, there are quite a lot of teaching staff who experience difficulties in involving students to be active in class. Today's students are quite vulnerable to the risk of disengagement due to competing priorities and also barriers to social interaction. The use of interactive technology can encourage active learning and also provide a much better facilitation of student experiences and inclusion. This case study aims to examine the practical implications of one interactive technology on student learning experiences. This research shows that the application of interactive technology to learning methods is able to have a real positive impact on the learning experience of students. Apart from that, achieving learning outcomes and also the level of motivation is one of the impacts that can be obtained. This helps students engage genuinely in assessment tasks and make their voices heard without fear or influence from faculty or peer pressure. The research also identified several challenges including the lead time needed to train teachers and students to use technology more effectively. This research contributes to existing knowledge by providing evidence-based implications of the use of interactive technologies in higher education.